Waste Pollution in Irrigation Channels: A Stakeholder Engagement Perspective from Simpang Tiga, Aceh Besar - Taufik, Taufik; Assagaf, Said Syamssiraj; Mahmuddin, Mahmuddin (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
This study aims to analyze stakeholder collaboration in managing irrigation waste in Simpang Tiga Subdistrict, Aceh Besar Regency. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analyses. These findings indicate the active involvement of the Environmental Agency, Water Resources Agency, NGOs, and local communities in waste management. This collaboration reflects a multi-stakeholder approach, which is essential for addressing complex environmental issues. However, challenges, such as low public awareness and limited funding, continue to hinder their effectiveness. This study recommends a more systemic collaborative approach, strengthened environmental education, and the inclusion of vulnerable groups to support sustainable and inclusive irrigation governance.